The Development of Controllable Magnetic Driven Microphysiological System - Yang, Jia-Wei; Chen, Yu-Wei; Ho, Pei-Yi; Jiang, Liane; Hsieh, Kuan Yu; Cheng, Sheng-Jen; Lin, Ko-Chih; Lu, Huai-En; Chiu, Hsien-Yi; Lin, Shien-Fong; Chen, Guan-Yu (Frontiers in Cell and Developmental Biology, 2019)
Current research has enabled the use of microphysiological systems and creation of models for alveolar and pulmonary diseases. However, bottlenecks remain in terms of medium- and long-term regulation of cell cultures and their functions in microchannel systems, as well as in the enhancement of in vitro representation of alveolar models and reference values of the data. Currently used systems also require on-chip manufacturing of complex units, such as pumps, tubes, and other cumbersome structures for maintaining cells in culture. In addition, system simplification and minimization of all external and human factors major challenges facing the establishment of in vitro alveolar models. In this study, a magnetically driven dynamic alveolus cell-culture system has been developed to use controlled magnetic force to drive a magnetic film on the chip, thereby directing the fluid within it to produce a circulating flow. The system has been confirmed to be conducive with regard to facilitating uniform attachment of human alveolar epithelial cells and long-term culture. The cell structure has been recapitulated, and differentiation functions have been maintained. Subsequently, reactions between silica nanoparticles and human alveolar epithelial cells have been used to validate the effects and advantages of the proposed dynamic chip-based system compared to a static environment. The innovative concept of use of a magnetic drive has been successfully employed in this study to create a simple and controllable yet dynamic alveolus cell-culture system to realize its functions and advantages with regard to in vitro tissue construction.